(untitled) (Prostor, 2023)
During the 1960s and 1970s, interdisciplinary collaborations among architects, designers, and artists represented an important aspect of Croatian architecture. This paper examines the institutional frameworks and conditions that facilitated such integrative practices. It recognizes the key participants and underscores a change in the underlying motives and other contributing factors for their collaborations across the decades. The paper also classifies the predominant building types resulting from such collaborations and prevalent social and political ambitions. Specific examples, such as institutional buildings, tourist facilities, and commercial buildings, illustrate the outcomes of these interdisciplinary endeavours. The analysis offers insights into the underlying factors and significance of these collaborations in shaping Croatian architectural practices during this period.